2020
DOI: 10.1016/j.jcot.2020.07.003
|View full text |Cite
|
Sign up to set email alerts
|

Bone marrow aspirate clot: A feasible orthobiologic

Abstract: Musculoskeletal disorders are one of the major health burdens and a leading source of disability worldwide, affecting both juvenile and elderly populations either as a consequence of ageing or extrinsic factors such as physical injuries. This condition often involves a group of locomotor structures such as the bones, joints and muscles and may therefore cause significant economic and emotional impact. Some pharmacological and non-pharmacological treatments have been considered as potential solutions, however, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
21
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 14 publications
(24 citation statements)
references
References 64 publications
0
21
0
Order By: Relevance
“…Thanks to its properties, the BMA clot behaves like an early hematoma, able not only to deliver new cells to the injury site but also to trigger an immunomodulatory cascade capable of attracting peripheral MSCs to the injury site. Nevertheless, to date, no studies evaluated the potential effects that aging could have on BMA clot biological properties ( Santos Duarte Lana et al, 2020 ). Since aging is accompanied by the increased incidence of bone diseases and reduced fracture-healing capacity, it is of key importance to evaluate orthobiologics’ properties in the aging population.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Thanks to its properties, the BMA clot behaves like an early hematoma, able not only to deliver new cells to the injury site but also to trigger an immunomodulatory cascade capable of attracting peripheral MSCs to the injury site. Nevertheless, to date, no studies evaluated the potential effects that aging could have on BMA clot biological properties ( Santos Duarte Lana et al, 2020 ). Since aging is accompanied by the increased incidence of bone diseases and reduced fracture-healing capacity, it is of key importance to evaluate orthobiologics’ properties in the aging population.…”
Section: Discussionmentioning
confidence: 99%
“…These data were also confirmed by an in vivo study by Lim and colleagues that underlined that the therapeutic potential of autologous bone graft and BMA clot in the repair of ulnar defects are similar, with the advantage of BMA clot being associated with a lower risk of complications ( Lim et al, 2019 ). A recent literature review further elucidates the characteristics found in BMA clot and its application in the clinical scenario ( Santos Duarte Lana et al, 2020 ). In this context, to confirm and strengthen data on the clinical use of BMA clot for bone regeneration, a pilot clinical study on clotted vertebral BMA is ongoing at our institution (Protocol: CVOD.…”
Section: Introductionmentioning
confidence: 99%
“…The use of anatomic landmarks for the average patient and ultrasound guidance for larger individuals may also be recommended. For the average patient, an ideal volume between 90 and 120 milliliters should be drawn, whereas in a large individual, volumes greater than 120–150 mL should be avoided [ 31 , 32 ].…”
Section: Bone Marrow Aspirate–technique and Contentmentioning
confidence: 99%
“…Thinking critically, adding too many chemicals or exogenous products to the BMA product might interfere in its natural biological potential. Additionally, in order to cause coagulation, platelet degranulation is a required step; this step delivers numerous osteotropic cytokines and growth factors into the site of injury [ 32 ]. Another fundamental effect that is often overlooked is the fibrinolytic activity.…”
Section: Coagulated Bma–potential Applicationsmentioning
confidence: 99%
See 1 more Smart Citation